Intake, ruminal fermentation parameters, and apparent total-tract digestibility by beef steers consuming Pensacola bahiagrass hay treated with calcium oxide. (17th December 2021) - Ciriaco, Francine M; Henry, Darren D; Schulmeister, Tessa M; Sanford, Carla D; Canal, Luara B; Fontes, Pedro L P; Oosthuizen, Nicola; Dubeux, Jose C B; Lamb, G Cliff; DiLorenzo, Nicolas
Abstract: To determine the effect of CaO-treated Pensacola bahiagrass ( Paspalum notatum ) hay on intake, ruminal fermentation parameters, and apparent total-tract digestibility of nutrients, nine ruminally cannulated Angus-crossbred steers were used in a triplicated 3 × 3 Latin square design. Steers had ad libitum access to either 1) untreated dry hay (DH ; n = 8); 2) hay at 50% DM treated with 8.9% CaCO3 (dry matter [DM ] basis; CC ; n = 9); or 3) hay at 50% DM treated with 5% CaO (DM basis; CO ; n = 8). Water was added to reach 50% DM in the CC and CO diets. Ruminal fluid and blood samples were collected every 3 h for 24 h. Ruminal fluid was analyzed for pH, volatile fatty acids (VFA ), and ammonia-nitrogen (NH 3 -N ). Blood was analyzed for plasma urea nitrogen (PUN ). Hay and fecal samples were collected for 4 d, four times daily for hay and twice daily for feces, to determine apparent total-tract digestibility of nutrients. The hay provided to steers during the digestibility period was analyzed for in vitro organic matter digestibility (IVOMD ) for 48 h. Data were analyzed as repeated measures for blood and ruminal fermentation parameters. Total DM intake was not affected ( P ≥ 0.674) by treatment. A treatment effect ( P < 0.001) was observed for average ruminal pH, where steers consuming CO had the greatest pH ( P < 0.001). Ruminal concentration of NH3 -N tended ( P = 0.059) to be reduced in steers consuming CO. There was a treatment × time interaction ( P = 0.023) on concentrations of PUN, where at 3 h DH and CO were lesser than CC ( P ≤ 0.050) and at 21 h DH was lesser than CC ( P = 0.020). Total VFA, acetate, propionate, butyrate, branched-chain VFA, and valerate concentrations were affected by treatment ( P ≤ 0.035), where a reduction ( P ≤ 0.034) occurred in steers consuming CO. No treatment differences were observed for total-tract digestibility of DM ( P = 0.186), organic matter ( P = 0.169), or crude protein ( P = 0.152); however, steers consuming DH had greater neutral detergent fiber ( P = 0.038) than CC and tended to be greater than CO ( P = 0.082). The CO hay had greater ( P = 0.005) IVOMD compared with DH and tended ( P = 0.100) to be greater than CC. Bahiagrass hay treated with CaO may reduce ruminal fermentation, as indicated by decreased total VFA concentration without altering DM intake. The addition of CaO did not improve the digestibility of bahiagrass hay in vivo; however, in vitro results are contradictory and warrant further elucidation. Lay Summary: With the ever-growing desire to increase efficiency in beef cattle production, researchers have developed strategies such as treating poor-quality forages with chemicals to increase the digestibility of fiber fractions, consequently increasing their energy value for cattle feeding. Calcium oxide has been proposed as a replacement to more caustic chemicals used in the past (e.g., NaOH) and data indicate that it can promote similar and effective outcomes. The current study evaluated the effects of bahiagrass hay treated with calcium oxide on ruminal fermentation parameters, apparent total-tract digestibility of nutrients, and intake by beef steers consuming hay ad libitum as the sole ingredient in their diet. Additionally, in vitro organic matter digestibility was evaluated on the hay provided to steers to assess treatment effectiveness. Results indicated that steers consuming bahiagrass hay treated with calcium oxide had 1) increased pH and reduced volatile fatty acids concentrations in the rumen; 2) reduced or tendency for reduction on total-tract digestibility of fiber fractions; and 3) no effect on intake, all when compared with steers consuming untreated hay. In contrast, in vitro results indicated that organic matter digestibility was increased when the forage was treated with calcium oxide. Abstract : Bahiagrass hay treated with calcium oxide may reduce ruminal fermentation in beef steers, without altering dry matter intake when the forage is the sole source of nutrients in the diet. However, it may still be a valid option based on in vitro results if protein supplementation is considered, potentially leading to positive effects of the treated forage.